PERTIMBANGAN HAKIM DALAM MEMUTUS PERKARA TINDAK PIDANA KORUPSI DANA BOS DI DINAS PENDIDIKAN LAMPUNG TENGAH (Studi Putusan Nomor 12/Pid.Sus-TPK/2022/PN.Tjk) - fernanda akbar; Bambang Hartono; zainudin hasan (Qistie Jurnal Ilmu Hukum, 2023)
ABSTRACT School Operational Assistance (BOS) is an effort by the Ministry of Education and Culture to support education funds for students at the elementary school (SD), junior high school (SMP) and senior high school (SMA) levels. School Operations Assistance (BOS) has been implemented since July 2005. This study aims to examine to find out and understand the basis for judges' considerations in deciding cases against perpetrators of corruption crimes, and mechanisms for returning state losses in corruption crimes. The approach used in this study is a normative juridical approach and this research uses a statutory approach, because various legal rules will be studied. Based on such considerations, the Panel of Judges concluded that the element "Which is detrimental to state finances or the country's economy", as stipulated in article 3 of Law Number 31 of 1999, concerning the Eradication of Corruption Criminal Penalties as amended and supplemented by Law Number 20 of 2001 concerning Amendments to Ri Law Number 31 of 1999 concerning the Eradication of Corruption Crimes has been fulfilled as a result of the defendant's actions. The mechanism for recovering State losses due to Corruption Crimes is carried out through court decisions and if the defendant is unable to recover state losses, the defendant will be subject to an additional period of confinement or if the defendant has property obtained from the conduct of the Corruption Act The Prosecutor's Office can auction the property. Keywords: School Operational Assistance, Corruption Crimes, Mechanisms.